An assessment of the impact of developmental dysplasia of the hip on patients' wellbeing: calculation of disability weight and country-specific utility weights. (1st March 2023) - Franco, Helena; Saxby, Nathan; Corlew, Daniel S.; Perry, Daniel C.; Pigeolet, Manon
Abstract : Aims: Within healthcare, several measures are used to quantify and compare the severity of health conditions. Two common measures are disability weight (DW), a context-independent value representing severity of a health state, and utility weight (UW), a context-dependent measure of health-related quality of life. Neither of these measures have previously been determined for developmental dysplasia of the hip (DDH). The aim of this study is to determine the DW and country-specific UWs for DDH. Methods: A survey was created using three different methods to estimate the DW: a preference ranking exercise, time trade-off exercise, and visual analogue scale (VAS). Participants were fully licensed orthopaedic surgeons who were contacted through national and international orthopaedic organizations. A global DW was calculated using a random effects model through an inverse-variance approach. A UW was calculated for each country as one minus the country-specific DW composed of the time trade-off exercise and VAS. Results: Over a four-month period, 181 surgeons participated in the survey, with 116 surgeons included in the final analysis. The global DW calculated to be 0.18 (0.11 to 0.24), and the country-specific UWs ranged from 0.26 to 0.89. Conclusion: This is the first time that a global disability weight and country-specific utility weights have been estimated for DDH, which should assist in economic evaluations and the development of health policy. The methodology may be applied to other orthopaedic conditions. Cite this article: Bone Jt Open  2023;4(3):120–128.